Tidal breathing parameters measured using structured light plethysmography in healthy children and those with asthma before and after bronchodilator. Issue 5 (8th March 2017) - Hmeidi, Hamzah; Motamedi‐Fakhr, Shayan; Chadwick, Edward; Gilchrist, Francis J.; Lenney, Warren; Iles, Richard; Wilson, Rachel C.; Alexander, John
Abstract: Structured light plethysmography (SLP) is a light‐based, noncontact technique that measures tidal breathing by monitoring displacements of the thoracoabdominal (TA) wall. We used SLP to measure tidal breathing parameters and their within‐subject variability (v) in 30 children aged 7–16 years with asthma and abnormal spirometry (forced expiratory volume in 1 sec [FEV1] <80% predicted) during a routine clinic appointment. As part of standard care, the reversibility of airway obstruction was assessed by repeating spirometry after administration of an inhaled bronchodilator. In this study, SLP was performed before and after bronchodilator administration, and also once in 41 age‐matched controls. In the asthma group, there was a significant increase in spirometry‐assessed mean FEV1 after administration of bronchodilator. Of all measured tidal breathing parameters, the most informative was the inspiratory to expiratory TA displacement ratio (IE50SLP, calculated as TIF50SLP /TEF50SLP, where TIF50SLP is tidal inspiratory TA displacement rate at 50% of inspiratory displacement and TEF50SLP is tidal expiratory TA displacement rate at 50% of expiratory displacement). Median (m) IE50SLP and its variability (vIE50SLP ) were both higher in children with asthma (prebronchodilator) compared with healthy children (mIE50SLP : 1.53 vs. 1.22, P < 0.001; vIE50SLP : 0.63 vs. 0.47, P < 0.001). After administration of bronchodilators to the asthma group, mIE50SLP decreased from 1.53 to 1.45 ( P = 0.01) and vIE50SLP decreased from 0.63 to 0.60 ( P = 0.04). SLP‐measured tidal breathing parameters could differentiate between children with and without asthma and indicate a response to bronchodilator. Abstract : Structured light plethysmography (SLP) is a noninvasive, noncontact technique that uses measurement of chest wall movement to derive indices of respiratory function. This study demonstrates that SLP can detect differences in respiratory function between normal children and children with asthma, and also in children with asthma pre‐ and postbronchodilator treatment. This technique may be useful in patients who are unable to perform conventional lung function tests.